The Use Of Mediation In The Settlement Of Public Private Partnerships Disputes - Sabela Gayo (International Asia Of Law and Money Laundering (IAML), 2023)
The purpose of this study was to analyze the position of the government in government cooperation agreements with business entities and how Alternative Dispute Resolution in KBBU. With normative juridical method, this study found that there is no clear legal basis related to the regulation of the government as a legal entity because Article 1653 of the Civil Code states the recognition of an association as a legal entity is mandatory through legislation; the position of the government is not explained in the general provisions of the PPP Presidential Regulation, but implicitly what the government means in PPP Presidential Regulation is ministries, institutions, and regions represented by Ministers, Heads of institutions and regional heads. Determination of Ministers/Heads of institutions/heads of Regions / BUMN and BUMD as PJPK based on authority in sectoral legislation; and the basis of binding balance in the position of the government as a party to the PPP agreement. So if there is a dispute in the PPP then naturally there is an alternative dispute resolution offered by using mediation as an alternative dispute resolution option.